Design of dense brush conformation bearing gold nanoparticles as theranostic agent for cancer - Verimli, Nihan; Demiral, Ayşegül; Yılmaz, Hülya; Çulha, Mustafa; Erdem, Sultan Sibel (Springer, 2019)
Dense brush conformation–bearing theranostic agents are emerging as drug delivery systems due to their higher ability to escape from reticuloendothelial system uptake which prolongs their in vivo circulation time. With the aim of developing dual therapy agent, 13-nm gold nanoparticles’ (AuNPs) surfaces were coated with different amounts of polyethylene glycol (PEG) (SH-PEG-NH2) to obtain dense brush conformation–bearing theranostic agents. Among the 14 different theranostic agent candidates prepared, the one hosting 1819 PEG per particle was selected as the most promising theranostic agent candidate based on structural conformation, stability, size, zeta potential, hemocompatibility, cell inhibition, and cell death pathway towards MCF-7 cell line. To test drug delivery efficiency of the developed PEGylated AuNP and to improve efficacy of the treatment, apoptotic peptide (AP) was covalently conjugated to NH2 terminus of the PEG in various ratios to yield AuNP-AP conjugate. Among the prepared conjugates, the one having 1 nmol of peptide per milliliter of AuNP yielded the most promising results based on the same criteria as employed for PEGylated AuNPs. Besides, incorporation of AP to AuNP returned in superior efficacy of AP since it was possible to achieve 50% cell death with 1000 times less amount of AP alone.
Keywords: Apoptosis; Apoptotic Peptide; Breast Cancer; Drug Delivery; Gold Nanoparticles; Hemocompatibility; Polyethylene Glycol; Theranostic Agent